Evaluation of the Regulation Changes on Environment and Forestry in Indonesia - Helmi, Helmi; Syam, Fauzi; Nopyandri, Nopyandri; Putra, Akbar Kurnia (Faculty of Law, Hasanuddin University, 2020)
This article aims to examine the correlation between the concept of proper enforcement of the law as stipulated in Article 5 (2) of the 1945 Constitution of Indonesia and the establishment and implementation of government regulation on environment and forestry. This article is a normative legal research with statute, historical, and conceptual approaches. The result shows that proper legal enforcement means two things, namely, establishment and enactment of government regulation by the President and the content of the regulation that does not contradict the law. Failure to comply with the law means the President does not establish or enforce a government regulation as mandated or the content of the regulation is not in line with the law.Â Â If the President does form or enforce the implementation of government regulation, this means that the President violates his oath and promise to uphold the Constitution and to serve the nation. If the content of the regulation contradicts with the law, it can be canceled. In this situation, the government needs to realign the content of existing regulations. The ministry involved in legal drafting is called to oversee the content and follow through with revisions. All party involves in the making of law and regulation, such as the People Representatives, the President, or the Minister, is reminded to carefully formulate a government regulation.